Do targeted hiring subsidies and profiling techniques reduce unemployment? - Elke J. Jahn; Thomas Wagner (Institute for the Study of Labor (IZA), 2008)
To reduce unemployment targeted hiring subsidies for long-term unemployed are often recommended. To explore their effect on employment and wages, we devise a model with two types of unemployed and two methods of search, a public employment service (PES) and random search. The eligibility of a new match depends on the applicant's unemployment duration and on the method of search. The hiring subsidy raises job destruction and extends contrary to Mortensen-Pissarides (1999, 2003) the duration of a job search, so that equilibrium unemployment increases. Like the subsidy, organizational reforms, which advance the search effectiveness of the PES, crowd out the active jobseekers and reduce overall employment as well as social welfare. Nevertheless, reforms are a visible success for the PES and its target group, as they significantly increase the service's placement rate and lower the duration of a job search via the PES.
urn:nbn:de:101:1-20081126232
Keywords: J41; 330; Matching model; hiring subsidy; endogenous separation rate; active labour market policy; PES; random search; Lohnsubvention; Arbeitsplatzsuchmodell; Arbeitsmarktpolitik; Arbeitsvermittlung; Theorie